Post occupancy evaluation of energy-efficient buildings in Tropical climates – Malaysia - Ng, Ban Huat; Akasah, Zainal Abidin (Archnet-IJAR, 2013)
There exists a well-known gap between occupants and building’s energy-efficient designs. A comprehensive building performance diagnostic technique, Post Occupancy Evaluation (POE) may surpass the current evaluation method by reducing the gap between occupants and building’s energy-efficient design. Due to these reasons, the aim of this research is to identify the problems with respect to energy-efficient design which affect occupants’ comfort. This research focuses on the application of energy-efficient design in office building and was conducted on energy-efficient buildings in Malaysia. A building performance survey framework, Energy-efficient Building Environmental Quality Questionnaire (EBEQ2), was used to identify the problems affecting occupants’ comfort and buildings’ Indoor Environmental Quality (IEQ). The result was analyzed using Statistical Package for Social Science (SPSS). The research outcome shows that majority of occupants are not satisfied with the thermal comfort and lighting condition of the buildings. Building certified with sustainable building rating tools does not guarantee better IEQ performance. Thus continuous research is needed to ensure energy-efficient building concept is applied effectively in each type of building.